Failures in implants - E Prashanti; Suresh Sajjan; Jagan Mohan Reddy (Indian Journal of Dental Research, 2011)
The burning problem that all the implantologists are confronted today is the complications and failures occurring with the treatment of osseointegrated implants. To further optimize the treatment outcome, etiologies and factors associated with implant failures should be elucidated. Conceivably such knowledge is needed for developing adequate treatment and prevention strategies. Hence, this paper is intended to provide an insight regarding various aspects of failures that affect dental implants.